PREVALENCE OF EXAMINATION RELATED ANXIETY IN A PRIVATE MEDICAL COLLEGE - Khan, Abdul Najeeb; Rasool, Sohail Ataur; Sultan, Ambreen; Tahira, Irum (Journal of Ayub Medical College Abbottabad, 2013)
Background: To assess examination related anxiety among first professional medical students and to determine the factors contributing to this kind of anxiety among them. Methods: A cross-sectional study using structured self-administered questionnaire was carried out over 10 days in Frontier Medical and Dental College, Abbottabad, in December 2012, using sample size of 200 students,. Survey questionnaire consisted of twenty questions regarding life style, study style, psychological and social problems, and results were analyzed by Visual Analogue Scale (VAS). Result: A total of 200 students out of 220 (90.90%) filled in the questionnaire. There were 61.50% male and 38.50% female students. The average maximum Examination related Anxiety marked on VAS was 47±21. Among different factors contributing to exam anxiety, inadequate rest (89%), irrational thoughts (67.50) and excessive course load (60%) were the most important factors reported by the students. Most of the students were aware of anxiety-reduction techniques but seldom implement them. Conclusion: On a VAS, examination, in its own right, has been established as a definite cause of anxiety, although the magnitude is not alarming. Students who regularly participate in class tests and perform well there, are least affected by this anxiety. Keywords: Anxiety, Visual analogue scale, inadequate rest